Odpowiedź :
4+(-6)+(+10)-(+8)-(-15) =4-6+10-8+15=29-14=15
-17+(-16)-(-17)-(-4)+(+12)=-17-16+17+4+12=0
[-(-9)-(-4)-(-10)-(-11)-(-16]-(50-13=(9+4+10+16)-(37)=39-37=2
-(-14)-5+6-26+24-14 =14-5+6-26+24-14=-31+30=-1
-17+(-16)-(-17)-(-4)+(+12)=-17-16+17+4+12=0
[-(-9)-(-4)-(-10)-(-11)-(-16]-(50-13=(9+4+10+16)-(37)=39-37=2
-(-14)-5+6-26+24-14 =14-5+6-26+24-14=-31+30=-1
4+(-6)+(+10)-(+8)-(-15) pierwsze
-17+(-16)-(-17)-(-4)+(+12)drugie
[-(-9)-(-4)-(-10)-(-11)-(-16]-(50-13)trzecie
-(-14)-5+6-26+24-14
pierwsze: 15
drugie: 0
trzecie: 38
ostatnie: -1
-17+(-16)-(-17)-(-4)+(+12)drugie
[-(-9)-(-4)-(-10)-(-11)-(-16]-(50-13)trzecie
-(-14)-5+6-26+24-14
pierwsze: 15
drugie: 0
trzecie: 38
ostatnie: -1